Fermentative Polyhydroxybutyrate Production from a Novel Feedstock Derived from Bakery Waste - Pleissner, Daniel (Hindawi Publishing Corporation, 2014)
In this study, Halomonas boliviensis was cultivated on bakery waste hydrolysate and seawater in batch and fed-batch cultures for polyhydroxybutyrate (PHB) production. Results demonstrated that bakery waste hydrolysate and seawater could be efficiently utilized by Halomonas boliviensis while PHB contents between 10 and 30% (w/w) were obtained. Furthermore, three methods for bakery waste hydrolysis were investigated for feedstock preparation. These include: (1) use of crude enzyme extracts from Aspergillus awamori, (2) Aspergillus awamori solid mashes, and (3) commercial glucoamylase. In the first method, the resultant free amino nitrogen (FAN) concentration in hydrolysates was 150 and 250 mg L(−1) after 20 hours at enzyme-to-solid ratios of 6.9 and 13.1 U g(−1), respectively. In both cases, the final glucose concentration was around 130–150 g L(−1). In the second method, the resultant FAN and glucose concentrations were 250 mg L(−1) and 150 g L(−1), respectively. In the third method, highest glucose and lowest FAN concentrations of 170–200 g L(−1) and 100 mg L(−1), respectively, were obtained in hydrolysates after only 5 hours. The present work has generated promising information contributing to the sustainable production of bioplastic using bakery waste hydrolysate.